Preparation and diagnosis of Schiff bases complex with component ions Co (II), Ni (II), Cu (II), Zn (II), Cd (II) derived from new amino acids - Thanaa Yousif (College of Education for Pure Sciences, 1999)
Abstract A new complexes of some transition metal ions (Co(II),Ni(II),Cu(II)) and non transition metal ions (Zn(II),Cd(II)) with a number of Schiff bases obtained from the condensation of some amino acids valine and serine with (Indol-3-carboxy aldehyde) have been prepared. All the prepared complexes have been characterized by elemental analysis(M), molar conductance, magnetic susceptibility infrared and electronic spectral. The complexes were classified as: A- mononuclear complexes. 1- Complexes with the formulas [ML(CH3COO) (H2O)2]. 2- Complexes with the formulas [ML(CH3COO)] H2O. B- Di nuclear complexes. Complexes with the formulas [M2(L)2(CH3COO)2] .2H2O. M= Co(II),Ni(II),Cu(II),Zn(II)Cd(II). L= Indol-3-carboxy aldehyde valine imine, Indol-3-carboxy aldehyde serine imine The physical measurements showed that the prepared complexes may have a tetra coordinated (tetrahedral or square planer) and hexa-coordinated (octahedral) structure and that all the prepared complexes were non electrolyte.